IMPROVING STUDENTS CREATIVE THINKING AND SELF EFFICACY THROUGH PROJECT-BASED LEARNING MODELS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
This study concuted at SMA Negeri 5 Kabupaten Tangerang. The porpose of this study was to determine the extent to which the application of the project based learning model of learning to improve the ability to think creatively and self efficacy. This study uses a Non-euivalent control group desgin hich is one of the research design that is part of a quasi experimental and data collection technique in form of tests, questionnaires, observation sheets, and documents. Samples were taken using the convenience sampling technique so that selected tenth grade IPS. The result of the calculation prove there is a significant difference and an increase between the ability of creative thinking and self efficacy of students who apply the project based learning with the creative thinking abilities of students ho apply conventional learning models in cooperative economic subjects. Based on the result of research usung the t-test then the results of testing the questionnaire with the average value that it can be concluded that there is a significant difference between students creative thinking abilities applying conventional learning models and increasing self efficacy of class students experiments that apply the project based learning model of learning in cooperative economic subjects.